Potential Deployment of Reversible Solid-Oxide Cell Systems to Valorise Organic Waste, Balance the Power Grid and Produce Renewable Methane: A Case Study in the Southern Italian Peninsula - Carbone, Claudio; Gracceva, Francesco; Pierro, Nicola; Motola, Vincenzo; Zong, Yi; You, Shi; Pérez-Fortes, Mar; Wang, Ligang; Agostini, Alessandro (Frontiers in Energy Research, 2021)
The large market penetration of non-dispatchable renewable power sources (vRES), i.e., wind and photovoltaic, may be hampered by an increasing need for large scale energy storage capacity and the challenges of balancing the power grid. Novel technologies integrating waste gasification with reversible Solid-Oxide Cell systems have been proposed to provide flexible grid balancing services. The rSOC system operated in electrolysis mode uses excess power from vRES to generate hydrogen (H2), which is combined with syngas derived from waste gasification to produce methane (CH4). The rSOC system can also be operated in fuel cell mode by oxidising syngas to produce electricity. This paper presents a well-defined case study which aimed to estimate the potential deployment of a novel rSOC technology in a future power system dominated by intermittent renewables. The hourly power grid residual loads (i.e., the difference between load and vRES power generation) and the availability of low-grade organic waste and residues are quantified and matched for the southern Italian peninsula in 2030. The results show that the theoretical grid flexibility needs approximately 10 TW h of overproduction and 5 TW h of underproduction in 2030 to ensure the complete disposal of the municipal organic waste generated in 2030 (6.7 Mt) and that production of renewable CH4 will need to be 1.4–2.4 Mt, pointing to an intriguing perspective for the deployment of rSOC systems at a large scale. The multifunctionality of the system proposed is an added value that can make it a convenient and efficient piece of the puzzle of technologies required in a climate-neutral and circular economy. The results and methods here presented are intended to form the basis for estimations of future potential deployment and economic and environmental assessments of competing technologies.